2010
DOI: 10.1090/s0002-9947-2010-04958-x
|View full text |Cite
|
Sign up to set email alerts
|

Stacks similar to the stack of perverse sheaves

Abstract: Abstract. We introduce, on a topological space X, a class of stacks of abelian categories we call "stacks of type P". This class of stacks includes the stack of perverse sheaves (of any perversity, constructible with respect to a fixed stratification) and is singled out by fairly innocuous axioms. We show that some basic structure theory for perverse sheaves holds for a general stack of type P: such a stack is locally equivalent to a MacPherson-Vilonen construction, and under certain connectedness conditions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…The stack property together with the MacPherson-Vilonen construction give an inductive strategy for computing categories of perverse sheaves. One of the motivations for the theory in this paper is to analyze this strategy systematically; see [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stack property together with the MacPherson-Vilonen construction give an inductive strategy for computing categories of perverse sheaves. One of the motivations for the theory in this paper is to analyze this strategy systematically; see [23].…”
Section: Introductionmentioning
confidence: 99%
“…This composition is strictly associative, and it has strict units, so this data defines a 2-category 2Funct(C, D). We define 2-natural transformations here; more details may be found in[11]:Definition B 23…”
mentioning
confidence: 99%
“…Ceci permettrait, par exemple, de décrire les faisceaux pervers sur un espace qui est localement un des espaces cités. Dans [9] et [8], D. Treumann utilise se genre de méthodes pour généraliser le procédé défini dans [6].…”
Section: Introductionunclassified
“…As an application , in [19], D. Treumann has used his description of the 2-category of constructible stacks and a description of the category of perverse sheaves given by MacPherson and Vilonen in [13] to characterize the stack of perverse sheaves and in the case of Thom-Mather spaces he has showed that if the stratum are 2-connected the category of perverse sheaves is equivalent to the category of finite-dimensional modules over a finite-dimensional algebra. As he has used a non explicit local description he does not obtain an explicit description.…”
mentioning
confidence: 99%